Zinc chalcogenide nanostructures: synthesis methodologies and applications—a review - Chatterjee, Anindita; Kumar, G. Kiran; Roymahapatra, Gourisankar; Das, Himadri Sekhar; Jaishree, G.; Rao, T. Siva (Frontiers in Nanotechnology, 2024)
Zinc chalcogenides nanostructures are important class of nontoxic nanomaterials due to their biocompatible nature, surface flexibility, high degree of crystallinity, high photoluminescence efficiency making them applicable in solar cells biosensors, photocatalysts, LED's and electroluminescence materials. There are various methods for the synthesis of Zinc chalcogenides including ZnS, ZnSe, ZnTe through colloidal, hydrothermal, solvothermal, microwave and core shell synthesis to prepare highly luminescent material for drug delivery and biomedical applications. The main focus of this review is to explore various synthetic approaches to tune the morphology, size and surface properties of zincbased chalcogenide nanostructures revealing their prospective as biocompatible quantum Dots. Despite advantages zinc chalcogenides have certain drawbacks too, having low mechanical strength, limited bandgap tunability and less thermal stability that can open the gateway for future research. Thus, this review may be proven beneficial for developing and designing of more advanced nanomaterials based on the existing knowledge, protocols and strategies